2019
DOI: 10.1007/978-3-319-98104-8
|View full text |Cite
|
Sign up to set email alerts
|

System Reengineering in Healthcare: Application for Hospital Emergency Departments

Abstract: The series "Studies in Systems, Decision and Control" (SSDC) covers both new developments and advances, as well as the state of the art, in the various areas of broadly perceived systems, decision making and control-quickly, up to date and with a high quality. The intent is to cover the theory, applications, and perspectives on the state of the art and future developments relevant to systems, decision making, control, complex processes and related areas, as embedded in the fields of engineering, computer scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…When undertaking multi-label research, the skills and talents of the personnel involved in health care can be found out [2]. To order to facilitate smooth operations within EDs, emergency departments require management [3] which gives leadership [2] to the followers. ED management must ensure better and revised quality of care and services over time [3].…”
Section: Future Research Directionsmentioning
confidence: 99%
See 3 more Smart Citations
“…When undertaking multi-label research, the skills and talents of the personnel involved in health care can be found out [2]. To order to facilitate smooth operations within EDs, emergency departments require management [3] which gives leadership [2] to the followers. ED management must ensure better and revised quality of care and services over time [3].…”
Section: Future Research Directionsmentioning
confidence: 99%
“…To order to facilitate smooth operations within EDs, emergency departments require management [3] which gives leadership [2] to the followers. ED management must ensure better and revised quality of care and services over time [3].…”
Section: Future Research Directionsmentioning
confidence: 99%
See 2 more Smart Citations